2016
DOI: 10.1103/physrevc.94.044314
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution inA100nuclei within the mapped interacting boson model based on the Gogny energy density functional

Abstract: The structure of even-even neutron-rich Ru, Mo, Zr and Sr nuclei in the A ≈ 100 mass region is studied within the interacting boson model (IBM) with microscopic input from the self-consistent mean-field approximation based on the Gogny-D1M energy density functional. The deformation energy surface in the quadrupole deformation space (β, γ), computed within the constrained HartreeFock-Bogoliubov framework, is mapped onto the expectation value of the appropriately chosen IBM Hamiltonian with configuration mixing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
85
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 70 publications
12
85
5
Order By: Relevance
“…Extensive discussions concerning shape evolution in the Kr, Zr and Sr isotopes have been carried out using covariant density functional theory (CDFT) within the relativistic HFB picture. Nomura et al [88] also showed that starting from the Gogny energy density No spectroscopic data are calculated but the mean-field is used to construct an IBM-CM Hamiltonian through a mapping of the energy surface onto the IBM-CM energy surface.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Extensive discussions concerning shape evolution in the Kr, Zr and Sr isotopes have been carried out using covariant density functional theory (CDFT) within the relativistic HFB picture. Nomura et al [88] also showed that starting from the Gogny energy density No spectroscopic data are calculated but the mean-field is used to construct an IBM-CM Hamiltonian through a mapping of the energy surface onto the IBM-CM energy surface.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…[24,25]. This work was supported by NuPNET and the German BMBF by Contracts 05P12PKNUF and 05P12DRNUP, the Spanish MINECO via Projects FPA2010-17142, CPAN (CSD 2007-00042) and PRI-PIMNUP-2011-1338 within the ERA-NET NuPNET call for translational joint activities, the UK STFC Contract No.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…These nuclei are among those with N ≃ 70 and A ≃ 110 which show interesting nuclear structure properties, such as drastic changes in shapes with A and shape coexistences [40,42,49,51,63,64,94,[124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141]. The structures of nuclei around N = 70 are also of particular interest for nuclear astrophysics because neutron-rich nuclei with A ≃ 110 are around the r-process path, which is determined by the equilibrium between neutron capture and photodisintegration [142][143][144][145][146][147][148][149][150][151][152].…”
Section: Resultsmentioning
confidence: 99%